Effect of Initial Water Temperature on the Performance of Air-source Heat Pump Water Heater System - Yuan Zhaoyang; Tao Leren; Yu Zhongyang (Zhileng xuebao)
When the air source heat pump water heater is heated to higher water temperature, the system efficiency will decrease obviously. In order to find out the reason of the decrease in heat efficiency and the operation rule of the system, this paper changes the initial water temperature, and studies the effect of temperature change on the parameters of the system. The results show that at the same initial water temperature, when the system operates, the COP has a slowly declining trend, which becomes violent later. With the different initial water temperature, because of the “preheating” stage and the affect by suction liquid of the compressor, the average COP decreases first and then increases with the uprise of the initial water temperature. In addition, a small amount of suction liquid can reduce exhaust temperature and improve system performance. But a large amount of suction liquid can increase the system power consumption, the decreased rate of COP will increase. This paper finally suggests that when the exhaust temperature drops again after the rise, the compressor begins to suction a large amount of liquid.